Ernest Gallaudet Draper papers - Draper, Ernest Gallaudet, 1885-1954.
Correspondence, diary, speeches, writings, notes, book reviews, biographical material, clippings, printed matter, and other papers relating primarily to Draper's service as U.S. assistant secretary of commerce and as a member of the Board of Governors of the Federal Reserve System (U.S.). Also documents his work with New York state and city agencies concerned with labor and unemployment and his service as a naval reserve officer during World War I. Subjects include banking, small business, business and democracy, the economy, foreign trade, trade agreements, defense, education, politics, and social welfare. His diary, titled "Stirring Times, 1941-1949" pertains to issues under consideration by the Board of Governors of the Federal Reserve System during World War II. Correspondents include Cordell Hull, Harold L. Ickes, Frances Perkins, Franklin D. Roosevelt, Daniel C. Roper, Harry S. Truman, and Fred M. Vinson.
Manufacturer and government official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hull, Cordell, -- 1871-1955 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Perkins, Frances, -- 1880-1965 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Vinson, Fred M., -- 1890-1953 -- Correspondence; United States. -- Department of Commerce; United States. -- Naval Reserve; Board of Governors of the Federal Reserve System (U.S.); Banks and banking; Business and politics; Commercial treaties; Democracy; Education; International trade; Labor and laboring classes -- New York (State) -- New York; Labor and laboring classes -- New York (State); Public welfare; Small business; Unemployment -- New York (State) -- New York; Unemployment -- New York (State); Unemployment; World War, 1914-1918.; World War, 1939-1945.; United States -- Commerce; United States -- Commercial policy; United States -- Defenses; United States -- Economic conditions -- 20th century; United States -- Economic policy -- 20th century; United States -- Politics and government -- 1901-1953.; United States -- Social conditions -- 20th century; Industrialists; Public officials